Stabilizing Copper(I) Complexes by Terminal Olefinic Side Arms and Studying Their Reactivity Towards Oxidation - Granichny, Alexander; Würtele, Christian; Schindler, Siegfried; Justus Liebig University Giessen (My University, 2025)
Many copper(I) complexes with aliphatic amine ligands have a strong tendency to disproportionate to copper(II) and elemental copper in solution at higher concentrations, making it difficult to isolate them and to study their reactivity. A series of copper(I) complexes with ligands based on tridentate N,N,N’,N’’,N’’-pentamethldiethylenetriamine (Me5dien) were synthesized that included terminal olefinic and aromatic groups. It could be shown that the olefinic side arms stabilized some of the copper(I) complexes. Whether and how strongly the complexes were stabilized depended on the position and length of the olefinic sidearm. Additionally, the reactivity of the copper(I) complexes towards dioxygen was investigated.
Keywords: ddc:540